Different Estimation Methods of the Stress-Strength Reliability Power Distribution - Selman, Bareq Baqe; Hamad, Alaa M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
This paper deals with estimation of the reliability system in the stress- strength model of the shape parameter for the power distribution. The proposed approach has been including different estimations methods such as Maximum likelihood method, Shrinkage estimation methods, least square method and Moment method. Comparisons process had been carried out between the various employed estimation methods with using the mean square error criteria via Matlab software package.